Strategic issues in public-private partnerships - Dewulf, Geert 540431; Blanken, Anneloes 540433; Bult-Spiering, Mirjam 540434 (Chichester, West Sussex ; Hoboken, N.J. : Wiley, 2012)
"Managing PPP projects is not a routine job, as every PPP project is different and should be managed accordingly. These projects require considerable capability and skills from both public sector and private sector managers involved, Strategic Issues in Public Private Partnerships, Second Edition, delivers the insight and tools necessary to assist those managers. As Public private partnership (PPP) arrangements become an increasingly popular way for national governments to fund and develop public infrastructure and urban areas with private sector contributions, a better understanding of the risks involved is crucial. The second edition of Strategic Issues in Public Private Partnerships : Provides an international overview of the application of concessions - the most common form of PPP [eg PFI (Private Finance Initiative); BO(O)T (Build/Own/Operate/Transfer) or DBFMO (Design/Build/Finance/ Maintain/Operate)]. Focusses on the introduction of concessions and the problems encountered, the solutions found for these problems, and the different approaches to concessions chosen across different countries. Provides a strategic overview for those involved in setting up and managing PPP projects. Illustrates lessons from different national backgrounds and gives managers the insight and tools to manage PPP projects effectively. Essential reading for Contractors & funding organizations involved in PPP projects as well as Researchers in construction management and public administration"--